Tidal Flats as a Significant Carbon Reservoir in Global Coastal Ecosystems - Chen, Zhao Liang; Lee, Shing Yip (Frontiers in Marine Science, 2022)
Tidal flats are widely distributed and provide a variety of ecosystem services. Nevertheless, the consequences of tidal flat loss and implications for services such as carbon (C) sequestration have not been assessed. In unvegetated tidal flat ecosystems, sediment is the most important carbon reservoir, similar to that of vegetated coastal wetlands (i.e., mangroves, salt marshes, and seagrass). We examined the C stocks and C accumulation rate (CAR) reported from 123 locations of tidal flat around the world and compared these results with data from mangroves, salt marshes, and seagrass meadows. The global average CAR of tidal flats is 129.8 g C m-2 yr-1, with the top-meter sediments containing on average 86.3 Mg C ha-1. Globally, tidal flat can bury 6.8 Tg C (24.9 Tg CO2) per year and can store 0.9 Pg C (3.3 Pg CO2) in the top meter sediment. Assuming the same rate of loss tidal flats as in the past three decades and that all disturbed sediment C is remineralized, 4.8 Tg C will be lost from tidal flat sediments every year, equivalent to an emission of 17.6 Tg CO2 to the water column and atmosphere.